Three regimens of procaine penicillin G, Augmentin, and probenecid compared for treating acute gonorrhoea in men. Issue 2 (April 1986) - Lim, K B; Thirumoorthy, T; Lee, C T; Sng, E H; Tan, T
Abstract : The efficacy of three penicillin regimens in treating uncomplicated gonorrhoea in men was evaluated. The regimens consisted of: Augmentin 3.25 g plus probenecid 1 g orally: aqueous procaine penicillin G 4.5 MIU intramuscularly and probenecid 1 g plus one tablet of Augmentin 375 mg orally; or aqueous procaine penicillin G 4.5 MIU intramuscularly and probenecid 1 g plus two tablets of Augmentin 375 mg orally. Cure rates for infections caused by penicillinase (beta lactamase) producing Neisseria gonorrhoeae (PPNG) were 87% (20/23) for regimen 1, 97% (28/29) for regimen 2, and 95% (19/20) for regimen 3. Thus the addition of one or two tablets of Augmentin 375 mg to aqueous procaine penicillin G and probenecid cured 96% (47/49) of infections caused by PPNG strains. All three regimens were 100% effective in eradicating infections caused by non-PPNG strains. Post gonococcal urethritis occurred in 24% of cases treated with regimen 1, 14% of cases treated with regimen 2, and 15% of cases treated with regimen 3. The geometric minimum inhibitory concentrations (MIC90) of Augmentin for 72 PPNG and 162 non-PPNG isolates of N gonorrhoeae obtained before treatment were 1.98 and 0.55 mg/l, respectively. Regimen 2, besides being effective against infections caused by PPNG or non-PPNG strains, has the advantage of cost effectiveness and low toxicity. This regimen may be useful in treating gonorrhoea in areas of high prevalence of PPNG strains, such as South East Asia and Africa.